Principles of management and administration - Bose, D. Chandra (PHI Learning, 2002)
This textbook on management is intended for students of B.Com (Pass and Hons.) and BBA courses. It provides a thorough treatment of the principles of management and presents a comprehensive analysis of the functional areas of management such as personnel, financial and marketing. Effective learning and assimilation of key concepts are facilitated through a systematic, in-depth and lucid treatment of the subject matter. This book will also be valuable to all those who are studying for professional qualifications such as MBA, CA, ICWA, and CS. The book consists of eight parts and a glossary: Part I: -- Introduction -- Provides an overview of key concepts of management, Part II: -- Planning, Part III: -- Organising and Staffing -- Emphasises traditional functions of management, Part IV: -- Direction and Controlling, Part V: -- Management in Future -- Outlines key futuristic thoughts, Part VI: -- Personnel Management -- Explains best practices, Part VII: -- Financial Management -- steps to implementation, Part VIII: -- Marketing Management -- potential benefits and pitfalls